A factor analytic study of the Childhood Trauma Questionnaire-Short Form in an all-female South African sample with and without HIV infection. (June 2019) - Spies, Georgina; Kidd, Martin; Seedat, Soraya
Abstract: Background: The Childhood Trauma Questionnaire-Short Form (CTQ-SF) is widely used around the world but no norms have been established for South African users of the CTQ. The CTQ has been employed in South Africa but not yet validated. The present study aims to address this gap. There is great need in both clinical and research settings for an assessment tool that adequately measures childhood trauma, a sensitive and challenging construct to measure. Objective: This study explores the psychometric properties of the CTQ-SF in an all-female cohort living with and without HIV infection in South Africa, the first study of its kind in this population. Participants and setting: The CTQ-SF was administered to 314 women (170 HIV uninfected; 144 HIV infected) in Cape Town, South Africa. Method: Internal consistency of the CTQ-SF was determined by Cronbach alpha coefficients. Using Lisrel, a confirmatory factor analysis (CFA) was performed, followed by an exploratory factor analysis (EFA) to explore an alternative factor structure model in this cohort. Results: For the group as a whole, the model fit was acceptable but not good. However, for the sub-sample of women living with HIV, the CFA revealed poor model fit. The EFA revealed a three-factor model, with mostly stable factor loadings for four of the five subscales. However, the Physical Neglect (PN) subscale cross loaded on two of the three factors. Conclusion: Our findings revealed an alternative factor structure from the original model in this study cohort. The PN subscale does not have stable factor loadings and is not homogenous. The original instrument may therefore benefit from revision for use in this population. Measures such as the CTQ can be informative for preventative strategies in HIV-infected or at-risk youth and for clinical interventions aimed at mitigating the negative psychological sequelae of childhood maltreatment.